Hydrochemistry and nutrients determined the distribution of greenhouse gases in saline groundwater - Li, Jiarui; Qian Chen; Ting Wang; Wang, HaiZhen; Ni, Jinren (Environmental PollutionEnvironmental Pollution, 2021)
The geography patterns and generation mechanisms of greenhouse gases (GHGs) in groundwater, especially in saline groundwater, are critical but rarely studied. Herein, we investigated the GHGs distribution in an aquifer, located upstream of Baiyangdian Lake, China, with a distinctive salinity gradient. A total of 132 groundwater samples were collected from 44 new-constructed wells along the lateral dimensions, and analyzed for dissolved GHGs concentrations, physiochemical parameters, and isotopes. The results showed that the dissolved CO2, CH4 and N2O concentrations ranged from 9.47 to 79.3 mg/L, 1.05-56.9 mu g/L, and 0.84-7.03 mu g/L, respectively. The groundwater was supersaturated with GHGs with respect to atmospheric equilibrium, suggesting groundwater discharge as a potential source of GHGs emission. CO2 significantly decreased while CH4 and N2O distinctively increased with the decline of total dissolved solids (TDS) concentration, illustrating an obvious spatial pattern in the GHGs distribution. The CO2 distributions mainly depended on the bicarbonate radical and TDS, indicating carbonate equilibrium as the main process involving in the CO2 generation. CH4 and N2O was primarily generated through the methanogenesis and denitrification processes, respectively. Nutrients including SO42- and total organic carbon predominately shaped the CH4 distributions, while nitrate mainly governed the N2O dis-tributions. Our study highlights the important roles of hydrochemistry and nutrients in the GHGs generation and distributions, which provides a significant insight on managing the GHGs emissions from the saline groundwater.